PELATIHAN PEMBELAJARAN JARAK JAUH DI MASA PANDEMI PADA MADRASAH IBTIDAIYAH SOROJUL ATHFAL IV DEPOK - Siti Marti’ah; Berta Dian Theodora (Bajang Institute, 2023)
The outbreak of a pandemic has disrupted face-to-face teaching and learning activities, closed physical access to and from the school environment to protect the safety of the souls of students and all school residents. Currently, teachers need to have more creativity and be flexible in the learning evaluation but still stick to the principles of inclusive teaching and learning. Learning evaluation can be interpreted as an activity in which the teacher collects data on the development of student learning abilities, assesses the learning process during the process, and measures whether the learning process has achieved its objectives. One of the evaluations has the aim of measuring student achievement after the learning process takes place so that when students experience difficulties during the learning process, the teacher can provide assistance in students' lack of understanding. Learning evaluation is carried out to measure the process and development of students on an ongoing basis as well as to understand the abilities and weaknesses of students, the results of the evaluation can provide information for parents/guardians of students